Lives of the Musicians - Krull, Kathleen; Nang Chan Yeema (Boston, New York, United State Houghton Mifflin Harcourt, 1993)
The Lives of twenty composers and musicians, ranging from Vivaldi, Mozart and Bach to Gershwin, Gilbert & Sullivan, and Woody Guthrie and profiled in this electric, humorous, and informative collection.
Keywords: Adult Nonfiction